Pengaruh Media Audio Visual Tentang Makharijul Huruf Terhadap Pemahaman Al-Qur’an di TPQ Darussalam Jatimulyo Alian Kebumen - Husna, Nasywa Muhimmatul; Fatimah, Siti (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
This research aims to determine the influence of the audio visual media makharijul letters on understanding the Al-Qur'an at TPQ Darussalam Jatimulyo Alian Kebumen. This research is in the form of Quantitative Research. The students studied were 20 TPQ Darussalam students. The method used in this research is a quantitative method. The type of research used was pre-experimental. The design of this research is a one group pre-test post-test design. The data collected was in the form of oral test data carried out by students in the Iqro' TPQ Darussalam class. The data analysis used is quantitative data analysis. The data analysis techniques used are prerequisite testing and hypothesis testing. Through the results of the analysis using the Mann Whitney U Test or Non-parametric Test, a significant value of 0.000 was obtained so it can be concluded that 0.000 < 0.05 and the hypothesis is accepted. Based on the research results, it can be concluded that there is an influence of audio visual media regarding makhorijul letters on understanding the Qur'an at TPQ DARUSSALAM Jatimulyo Alian.